Occupational radiation exposure and thyroid cancer incidence in a cohort of U.S. radiologic technologists, 1983–2013. Issue 9 (2nd February 2018) - Kitahara, Cari M.; Preston, Dale L.; Neta, Gila; Little, Mark P.; Doody, Michele M.; Simon, Steven L.; Sigurdson, Alice J.; Alexander, Bruce H.; Linet, Martha S.
Abstract : Although childhood exposure to ionizing radiation is a well‐established risk factor for thyroid cancer, the risk associated with adulthood exposure remains unclear. We prospectively examined the association between cumulative, low‐to‐moderate dose occupational radiation exposure to the thyroid and thyroid cancer incidence in the U.S. Radiologic Technologists cohort. The study included 89, 897 members who completed at least two of four mailed questionnaires and were cancer‐free at the time of the first questionnaire. Cumulative occupational thyroid radiation dose (mean = 57 mGy, range = 0–1, 600 mGy) was estimated based on self‐reported work histories, historical data and, during the years 1960–1997, 783, 000 individual film badge measurements. During follow‐up, we identified 476 thyroid cancer cases. We used Poisson regression to estimate excess relative risk of thyroid cancer per 100 milliGray (ERR/100 mGy) absorbed dose to the thyroid gland. After adjusting for attained age, sex, birth year, body mass index and pack‐years smoked, we found no association between thyroid dose and thyroid cancer risk (ERR/100 mGy = −0.05, 95% CI <–0.10, 0.34). In this large cohort study of radiologic technologists, protracted, low‐to‐moderate dose ionizing radiation exposure to the thyroid gland in adulthood was not associated with an increased risk of thyroid cancer. Abstract : What's new? Exposure to ionizing radiation is a known risk factor for thyroid cancer. Little is known, however, about the impact of low‐to‐moderate cumulative occupational radiation exposure on thyroid cancer risk. In the present evaluation, radiation doses to the thyroid were reconstructed based on badge dose readings and work history for U.S. radiologic technologists and on literature review. The results show no association between cumulative occupational radiation thyroid dose and thyroid cancer incidence after adjusting for multiple risk factors, including age, sex and body mass index. The findings help clarify the role of adulthood radiation exposure in thyroid cancer development.